Survival rates with external beam radiation therapy in newly diagnosed elderly metastatic prostate cancer patients. Issue 1 (11th October 2021) - Wenzel, Mike; Collà Ruvolo, Claudia; Würnschimmel, Christoph; Nocera, Luigi; Tian, Zhe; Saad, Fred; Briganti, Alberto; Tilki, Derya; Graefen, Markus; Becker, Andreas; Roos, Frederik; Mandel, Philipp; et al.
Abstract: Background: The survival benefit of primary external beam radiation therapy (EBRT) has never been formally tested in elderly men who were newly diagnosed with metastatic prostate cancer (mPCa). We hypothesized that elderly patients may not benefit of EBRT to the extent as younger newly diagnosed mPCa patients, due to shorter life expectancy. Methods: We relied on Surveillance, Epidemiology and End Results (2004–2016) to identify elderly newly diagnosed mPCa patients, aged >75 years. Kaplan–Meier, univariable and multivariable Cox regression models, as well as Competing Risks Regression models tested the effect of EBRT versus no EBRT on overall mortality (OM) and cancer‐specific mortality (CSM). Results: Of 6556 patients, 1105 received EBRT (16.9%). M1b stage was predominant in both EBRT ( n = 823; 74.5%) and no EBRT ( n = 3908; 71.7%, p = 0.06) groups, followed by M1c ( n = 211; 19.1% vs. n = 1042; 19.1%, p = 1) and M1a ( n = 29; 2.6% vs. n = 268; 4.9%, p < 0.01). Median overall survival (OS) was 23 months for EBRT and 23 months for no EBRT (hazard ratio [HR]: 0.97, p = 0.6). Similarly, median cancer‐specific survival (CSS) was 29 months for EBRT versus 30 months for no EBRT (HR: 1.04, p = 0.4). After additional multivariable adjustment, EBRT was not associated with lower OM or lower CSM in the entire cohort, as well as after stratification for M1b and M1c substages. Conclusions: In elderly men who were newly diagnosed with mPCa, EBRT does not affect OS or CSS. In consequence, our findings question the added value of local EBRT in elderly newly diagnosed mPCa patients.